Intravenous Mistletoe Treatment in Integrative Cancer Care: A Qualitative Study Exploring the Procedures, Concepts, and Observations of Expert Doctors. (24th April 2016) - Kienle, Gunver S.; Mussler, Milena; Fuchs, Dieter; Kiene, Helmut
Abstract : Background . Mistletoe therapy (MT) is widely used in patient-centered integrative cancer care. The objective of this study was to explore the concepts, procedures, and observations of expert doctors, with a focus on intravenous MT. Method . A qualitative interview study was conducted with 35 highly experienced doctors specialized in integrative and anthroposophic medicine. Structured qualitative content analysis was applied. For triangulation, the results were compared with external evidence that was systematically collected, reviewed, and presented. Results . Doctors perform individualized patient assessments that lead to multimodal treatment approaches. The underlying goal is to help patients to live with and overcome disease. Mistletoe infusions are a means of accomplishing this goal. They are applied to stabilize disease, achieve responsiveness, induce fever, improve quality of life, and improve the tolerability of conventional cancer treatments. The doctors reported long-term disease stability and improvements in patients' general condition, vitality, strength, thermal comfort, appetite, sleep, pain from bone metastases, dyspnea in pulmonary lymphangitis carcinomatosa, fatigue, and cachexia; chemotherapy was better tolerated. Also patients' emotional and mental condition was reported to have improved. Conclusion . Individualized integrative cancer treatment including MT aims to help cancer patients to live well with their disease. Further research should investigate the reported observations.